59.7k views
7 votes
PLEASE ANSWER ASSP!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!

PLEASE ANSWER ASSP!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!-example-1
User Dalex
by
4.9k points

1 Answer

7 votes
Answer: p=4.1

Step by step explanation:
7(p-9)=-34.3 Divide both sides of the equation by 7

P-9=-4.9 Move the constant to the right hand side and change its sign

P=-4.9+9 Calculate the sum

P=4.1
User Moses
by
5.0k points